Arranging and Performance Techniques of Traditional Chinese Musical Works for the Electone - Yilin , Ding; Pattananon, Nicha (Journal of Roi Kaensarn Academi, 2024)
The electone, which was introduced to China in the 1980s, is often referred to as a "one-man symphony" due to the gradual application of electronic technology in a variety of fields. Its ability to mimic the sounds and playing styles of Western musical instruments has reached such a high level of perfection that it is often regarded as a "one-man symphony". In recent years, the emergence of China’s Nine Moon Wonders has led to a gradual understanding of the electone by the majority of Chinese families. However, its popularity in China remains limited compared to that of Western classical instruments such as the piano and violin. In contrast to the piano work "Piccolo for Shepherd Boys" by Mr. He Luting, which exhibits a distinctive and mature Chinese style, and the violin concerto "Liang Zhu " by Mr. He Zhanhao and Mr. Chen Gang, which is based on the Yueju opera "Liang Shanbo and Zhu Yingtai", the electone lacks similar ethnic music works that have a distinctive Chinese style and are based on ethnic tunes. In concerts and major music competitions, competitors tend to select works that are more oriented towards Western music or Japanese pop music, with a corresponding lack of opportunities to showcase and promote Chinese folk music.